Florestan Fernandes and Guerreiro Ramos in the construction of an idea of ​​modern Brazil - Martins, Tatiana (2006)
This work has as objective to demonstrate the way for which two Brazilian sociologists, Florestan Fernandes and Guerreiro Ramos, in the years 50 and beginning 60, constructed two conceptions of Modern Brazil through its theoretical pressupositions, understood as form of construction of a Brazilian Sociology. Of this form, the work searchs to associate this attempt of construction of the foundations of a Brazilian Sociology with the proper process of national development and, mainly, with the formulation of a National Project.